Retention of cinnamaldehyde in poly(vinyl alcohol) films intended for preservation of faba beans through vapor-phase antimicrobial effect. (September 2021) - Kardam, Saurabh Kumar; Kadam, Ashish A.; Dutt, Dharm
Graphical abstract: Highlights: Vapor-phase antimicrobial efficacy of cinnamaldehyde/PVOH films was tested. The films strongly inhibited Escherichia coli and Bacillus subtilis, in vapor-phase. The films with higher cinnamaldehyde content sorbed relatively less moisture. A cinnamaldehyde content of 5.59 μL/g film preserved faba beans for 4 days at 25 °C. Abstract: Vapor-phase antimicrobial activity of cinnamaldehyde (CINN) loaded poly(vinyl alcohol) (PVOH) films was assessed against the gram-positive (+ ve) bacterium Bacillus subtilis and the gram-negative (- ve) bacterium Escherichia coli . CINN retention in the film was studied via a facile method based on UV–vis spectroscopy. It was found that merely 5.59 μL CINN/g film retained in the film was sufficient to preserve faba beans pods up to 4 days at 25 °C. At this low concentration of CINN, the properties of the CINN/PVOH films like morphology, mechanical strength, composition, and color largely remained unperturbed. Upon exposure to 55 % RH, the integrity of the antimicrobial CINN/PVOH film was not compromised at the end of 137 days, allowing the film to be used at this condition.